Modeling of P-Loss Risk and Nutrition for Mango (Mangifera indica L.) in Sandy Calcareous Soils: A 4-Years Field Trial for Sustainable P Management - Jiyue Wang; Mohssen Elbagory; Yingdui He; Xu Zhang; Yongyong Hui; Mamdouh A. Eissa; Zheli Ding; Sahar El-Nahrawy; Alaa El-Dein Omara; Medhat G. Zoghdan; Ahmed M. S. Kheir (Horticulturae, 2022)
The continuous addition of phosphorus (P) fertilizers above plant requirements increases P loss risks, especially if such fertilization practices continue long-term. The current study aims to determine the threshold value of P in plants and soil, which achieves the maximum mango fruit yield without P loss risk. P fertilizer doses (0–240 g tree−1) were added to 12-year-old mango (Mangifera indica L.) cv Hindy planted in sandy soil for four consecutive years. Soil and plant samples were collected each year to estimate the critical p values by linear–linear, quadratic, and exponential models. The relationships between fruit yield and available soil P were positive and significant in all the mathematical models. Mango fruit yield is expected to reach its maximum value if the sandy calcareous soil contains an available P amount ranging between 10–12 mg kg−1 and increasing the soil available P above this level leads to negligible increases in the fruit yield. Increasing the available soil P above 20.3 mg kg−1 increases P-loss risk. P concentrations in blades and petioles of mango leaves can be arranged as follows: beginning of the flowering stage > the full blooming stage > beginning of the fruiting stage. The analysis of petioles of mango leaves in the beginning of the flowering stage significantly corelated with mango fruit yield and can be used in predicting the response of mango to P fertilization. The findings of the present investigation revealed that the critical P in mango petioles ranged between 2.34 and 3.53 g kg−1. The threshold of available soil P for maximum fruit yield is half of P loss risks. The combined analysis of soil and plants is a powerful diagnostic tool for P management in sandy degraded soil. The findings of the current study are a good tool in achieving the optimum utilization of P fertilizer resources in maximizing mango fruit yield and reducing the risks of environmental pollution that result from excessive fertilization doses.